Gestão da política de assistência social: implicações na garantia de proteção social um estudo no município de Votuporanga - SP - Magri, Anoel Junior (2014)
This study analyzes the operationalization of the welfare policy from the county of Votuporanga SP, having as its basis the non-contributive social protection management, in the post SUAS Sistema Único de Assistência Social period. In order to establish the historical, theoretical-conceptual and legal-normative referent and enable the comprehension of dynamics and direction given to welfare policy management, welfare s institutionalization and organization as a policy are contextualized, whilst Social Stability, having the social protection assurance to all citizens as an objective. It presents, likewise, the competences and guidelines defined to the welfare policy management and to the social-assistencial actions supply, accordingly preconized by LOAS Lei Orgânica de Assistência Social. This study has as its holder an empiric research carried out with the manager and with the professionals who work at management level in the Welfare Secretariat in Votuporanga. This research has in view characterizing welfare management in the county, identifying and analyzing the welfare management procedures, the topmost challenges currently faced in their welfare offer to citizens and their approach towards it. In this research, it is evinced the importance of improving management processes performed by the county, in order to enable that it is democratic and effective, whilst offering programs, services and benefits from its social-assistencial net